We are okay - LaCour, Nina (New York, NY : Dutton Books, 2017)
After leaving her life behind to go to college in New York, Marin must face the truth about the tragedy that happened in the final weeks of summer when her friend Mabel comes to visit.
Keywords: College students -- Fiction; Grief -- Fiction; Friendship -- Fiction; College students -- Fiction; Bereavement -- Fiction; Friendship -- Fiction